Design and synthesis of a stable-performance P2-type layered cathode material for sodium ion batteries. Issue 60 (8th June 2016) - Liu, Shuo; Jiang, Xiaolei; Zhang, Junshu; Yang, Jian; Qian, Yitai
Abstract : P2-type Na0.6 Ni0.2 Co0.2 Mn0.5 Ti0.1 O2 powders are successfully synthesized by a solid state reaction. Ex situ XRD reveals the phase transition process occurs at 4.1 V. Abstract : P2-type Na0.6 Ni0.2 Co0.2 Mn0.5 Ti0.1 O2 powders are successfully synthesized by a solid state reaction. Ex situ XRD reveals the phase transition process from P2 to O2 occurs at 4.1 V. As they are cycled in a narrow voltage window (4.2–2 V), they exhibit excellent cycling stability and high rate capability. Even at 5C for 250 cycles, the reversible capacity could be kept at 66.0 mA h g −1 .